PENGARUH LINGKUNGAN KERJA, MOTIVASI, DAN KERJASAMA TIM TERHADAP PRESTASI KERJA GURU DAN KARYAWAN - Rahmadani, Kenyshia Afifah Disty; Kusdiyanto, Kusdiyanto (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to analyze the effects of work environment, motivation, and teamwork on the productivity of instructors and workers. This quantitative analysis used data from 130 workers. This inquiry uses purposive sampling as its methodology. The study's results demonstrate that the work environment, motivation, and Teamwork each have a positive and significant influence on job performance. Keywords: Work Environment; Motivation; Teamwork, Work Performance